SIMULASI PROSES BONGKAR MUAT PETI KEMAS DI PT. PELABUHAN INDONESIA SORONG - Josua Istia; Trytia Arungpadang; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
PT. Pelindo Sorong is a company in West Papua that offers loading and unloading services using containers. Although the company has implemented  a queue distribution pattern in handling containers, it needs process improvement.One method to overcome is problem is to use Promodel 2016 software and SPSS version 22 as a tool to determine the optimal timing of the ideal loading and unloading process. The container handling equipment observed in this study were a crane, tractor trailer and reach stacker. The field survey in February 2020 was conducted to measure the handling time of dry containers.The simulation results show that the optimal average loading process is 2.32 minutes and the loading process time is 3.08 minutes. And the highest level of utility for the loading process is 25.24% and for the loading process is 53.30%. From the analysis using promodel 2016 software, it is known that the highest utility value of the two processes is below 100% so that there is no bottleneck. If the utility value of both processes reaches 100%, there will be a rush in the queue system. The solution is the there must be additional tools in the process with a high level of utility.Keywords: Containers, Loading and unloading equipment, Promodel 2016, Optimal    average time